Performance Analysis of Ammonia Converter in Ammonia Unit Factory - Susmanto, Prahady; Dewantara, Dino; Widodo, Teguh; Susanti, Susi (CHEESA: Chemical Engineering Research Articles, 2023)
An ammonia converter is a catalyzed reactor that facilitates the synthesis of NH3 (ammonia) from hydrogen (H2) and nitrogen (N2). Several studies have shown that the performance of this reactor significantly influences the operational efficiency and productivity of ammonia plants. Therefore, this study aims to evaluate the performance of an ammonia converter by assessing the effect of operating conditions on the reactant conversion and reaction products using design and actual data. The operating conditions examined included temperature, pressure, ratio of reactants, and inert mole utilized during the NH3 synthesis process. The results showed that the highest NH3 yield of 20.28% was achieved in actual data with 351.5oC temperature, 154.32 kg/cm2 pressure, 3.58 raw material ratio, and 3.57% inert mole (sixth dataset). The performance efficiency of an ammonia converter can be assessed using temperature, reactant ratio, and inert moles, while the pressure factor was insignificant due to dataset fluctuations. Based on the evaluation results, the converter experienced a decrease in performance due to a discrepancy in the existing operating conditions between the design and actual data.